CUSTOMS AND TRADITIONS RELATED TO MOURNING OF THE KARAKALPAKS - Dauletmuratov Bayrambay Jenisbaevich (Web of Journals Publishing, 2025)
The mourning customs of the Karakalpaks living on the shores of the Aral Sea and their transformation are discussed in this article.
Keywords: Customs and traditions, mourning, mourning clothes, to mourn, guest food.